Rule induction for financial modelling and model interpretation - (:unkn) unknown (IEEE Computer Society, 1995)
The paper discusses the possibility of applying a specific rule induction algorithm, ID3 to various financial data analysis tasks. These tasks include not only model building but also interpreting the outputs of financial models. The algorithm is shown to have major drawbacks as a modelling tool, some of which carry over to the post processing task. The fact that financial variables are often measured on a ration scale also causes problems. The paper examines solutions to the key problems and provides the basis on which analysts can judge the suitability of the algorithm for their own applications. © 1995 IEEE.